Detection of Cytomegalovirus, Rubella virus, and IL-2 Levels in a Sample of Recurrently Aborted Iraqi Women - S. Saleh, Duhua; E. Kharibet, Kawthar (Iraqi Journal of Science, 2023)
The present study aimed to investigate CMV and Rubella virus as a causative agent of recurrent abortion, while the IL-2 levels were estimated as immune parameter during pregnancy period. A total of 63 blood samples were collected from recurrently aborted women, control non-pregnant women and control pregnant women. The results recorded 72.09 % CMV positive aborted women and 27.91 % Rubella virus positive aborted women. Levels of IL-2 were (437.03 ± 38.02) pg/ ml in first group, (390.51± 63.56) pg/ ml in second group, (32.98 ±15.12) pg/ ml in control group non pregnant women and (118.63 ± 24.81) pg/ ml in control pregnant women. High IL-2 levels in all studied women indicate presence of a factor affecting the immune system other than viral infection or pregnancy which may be needing more investigations.